Understanding Extension for School-Based Agricultural Education #1: Extension 101 - Debra Barry; John Diaz; Alyssa Shepherd; Jennifer Patton; Stephen Gran (EDIS)
This article and series were designed primarily for use by secondary agriscience teachers in school-based agricultural education programs (SBAE) to help build a strong understanding of Extension and the role of Extension professionals. An important part of access and use of Extension services is understanding its background, structure, and function. This initial publication in the Understanding Extension for School-Based Agricultural Education series provides agricultural educators and the general public with a basic understanding of Extension. This new 4-page publication of the Department of Agricultural Education and Communication was written by Debra Barry, John Diaz, Alyssa Shepherd, Jennifer Patton, and Stephen Gran. https://edis.ifas.ufl.edu/wc372